The Case for Evidence-Based Outdoor Recreation Interventions for Girls: Helping Girls "Find Their Voice" in the Outdoors - Kate Evans; Kellie Walters; Denise Anderson (MDPI AG, 2020)
Females' participation in outdoor recreation is often limited for a variety of reasons including social gender norms, a lack of exposure, and fear. Research has uncovered a wide range of positive outcomes for those females who do participate ranging from enhanced self-esteem and confidence to improved body image, indicating the importance of opening the outdoors as a welcoming place for all to experience. Finding Your Voice is a recreation intervention created with the focus of introducing middle school girls to outdoor recreation to increase the participants' self-efficacy and self-empowerment. Empirical research focusing on participant experiences has demonstrated promising results and the best practices from Finding Your Voice and the broader research on female empowerment in the outdoors are presented.